2017
DOI: 10.12688/f1000research.10442.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the serotonin receptor 7 (HTR7) gene are associated with cortisol levels in African American young adults

Abstract: Serotonin is a neurohormone involved in biological processes, Introduction: such as behavior and immune function. Chronic psychosocial stressors may cause serotonin release resulting in immune system dysregulation, as evidenced by increased or far decreased levels of cortisol, a blood biomarker of stress and immune function. We hypothesize that genetic polymorphisms in the gene are associated with both hypo-and hyper-cortisolism. HTR7Methods: The study population included 602 African American subjects between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several reports have described variants in the 5-HT 7 receptor gene in humans with alcoholism 36 and cortisol levels in African American adults. 37 We could find no studies that investigated associations of 5-HT 7 receptor variants with aspects of the cardiovascular system. Do the 5-HT 2A and 5-HT 7 Receptor Physically Interact?…”
Section: -Ht 7 Receptor Antagonism Unmasks 5-ht But Not Tcb-2 or Nboh...mentioning
confidence: 99%
“…Several reports have described variants in the 5-HT 7 receptor gene in humans with alcoholism 36 and cortisol levels in African American adults. 37 We could find no studies that investigated associations of 5-HT 7 receptor variants with aspects of the cardiovascular system. Do the 5-HT 2A and 5-HT 7 Receptor Physically Interact?…”
Section: -Ht 7 Receptor Antagonism Unmasks 5-ht But Not Tcb-2 or Nboh...mentioning
confidence: 99%
“…HTR7 knock-out mice or mice with pharmacological blockade of HTR7 showed antidepressant-like behavior (13-16). A recent study showed genetic polymorphisms in HTR7 were associated with hypocortisolism in a gender specific manner in African American subjects, suggesting HTR7 may contribute to stress system dysregulations (17). Emerging preclinical evidence have suggested that HTR7 is involved in the action of antidepressants.…”
Section: Introductionmentioning
confidence: 99%